Theologising with the Sacred 'Prostitutes' of South India : Towards an Indecent Dalit Theology - Parker, Eve Rebecca, (Currents of Encounter ;, 2021)
"In Theologising with the Sacred 'Prostitutes' of South India, Eve Rebecca Parker theologises with the Dalit women who from childhood have been dedicated to village goddesses and used as 'sacred' sex workers. Parker uses ethnographic, anthropological, theological, hermeneutical and historical research and analysis in order to critically engage with the lived religiosity and daily struggles of the dedicated women, known as devadāsīs. In doing so, she works towards an Indecent Dalit Liberation Theology that challenges systems of oppression and cultures of impunity, including casteism, sexism, classism and a history of socio-political and religious marginalisation. The result is a profound theologising of struggle and resistance with the sexual narratives of the oppressed"--